Italy : Financial Sector Assessment Program; Detailed Assessment of the Observance of Monte Titoli of the CPSS/IOSCO Recommendations for Securities Settlement Systems. (IMF Staff Country Reports; Country Report, 2006)
This paper discusses a Detailed Assessment of the Observance of Monte Titoli (MT) for Securities Settlement Systems for Italy. The paper discusses that the rules and regulations governing the operations and activities of MT are public and accessible to participants. The Italian laws and regulations of Banca d'Italia (BI) and Consob provide a sound legal basis for the enforcement of transactions by defining the terms and conditions, and the rights and obligations of the involved counterparties as well as the obligations of MT toward their participants.